Lower rates of mortality, readmission and reoperation in patients receiving acupuncture after hip fracture: a population-based analysis. Issue 5 (October 2020) - Lin, Jeff Chien-Fu; Lin, Tzu-Chieh; Cheng, Chi-Fung; Lin, Ying-Ju; Liang, Sophia; Chang, Yu-Jun; Liang, Wen-Miin
Background: Studies on the effects of acupuncture on mortality and complication rates in hip fracture patients are limited by small sample size and short follow-up time. We aimed to assess the associations of acupuncture use with mortality, readmission and reoperation rates in hip fracture patients using a longitudinal population-based database. Methods: A retrospective matched cohort study was conducted using data for the years 1996–2012 from Taiwan's National Health Insurance Research Database. Hip fracture patients were divided into an acupuncture group consisting of 292 subjects who received at least 6 acupuncture treatments within 183 days of hip fracture, and a propensity score matched "no acupuncture" group of 876 subjects who did not receive any acupuncture treatment and who functioned as controls. The two groups were compared using survival analysis and competing risk analysis. Results: Compared to non-treated subjects, subjects treated with acupuncture had a lower risk of overall death (hazard ratio (HR): 0.41, 95% confidence interval (CI): 0.24–0.73, p  = 0.002), a lower risk of readmission due to medical complications (subdistribution HR (sHR): 0.64, 95% CI: 0.44–0.93, p  = 0.019) and a lower risk of reoperation due to surgical complications (sHR: 0.62, 95% CI: 0.40–0.96, p  = 0.034). Conclusion: This is the first study to suggest that postoperative acupuncture in hip fracture patients is associated with significantly lower mortality, readmission and reoperation rates compared with those of matched controls.